Gender Differences in Mathematics Self-concept Across the World: an Exploration of Student and Parent Data of TIMSS 2015 - Mejía-Rodríguez, Ana María; Luyten, Hans; Meelissen, Martina R. M. (International journal of science and mathematics education, 2021)
Using data from the Trends in International Mathematics and Science Study (TIMSS) 2015 assessment of fourth-grade students in 32 countries, a series of mean comparisons and regression analyses were conducted to determine (1) the gender gap in students’ self-concept in mathematics; (2) to what extent student achievement, student gender, and parental characteristics (early numeracy activities, attitudes, expectations, and education) are related to students’ self-concept; and (3) to what extent the effect of achievement and parental characteristics on mathematics self-concept differs between male and female students. Results from this study indicate that gender differences in students’ self-concept in mathematics are significant in most countries, usually in favour of boys as early as in fourth grade. The differences largely remain the same when the data analysis controls for effects of student achievement and parental involvement.